2016
DOI: 10.1007/s12542-016-0311-y
|View full text |Cite
|
Sign up to set email alerts
|

The first description of a microtrombidiid mite (Actinotrichida: Prostigmata, Microtrombidiidae) from Baltic amber, with notes on related extant genera and species

Abstract: Discovery of parasitengone mites (Acari) in the Gulf of Gdańsk deposits of Baltic amber (“Blue Earth” sediment) resulted in the first description of a fossil representative of Microtrombidiidae. The new species, based on larvae, displays affinity to recent members of Montenegtrombium Saboori and Pešić, 2006, Persianthrombium Sedghi, Saboori and Hakimitabar (in Sedghi et al. 2010) and Porttrombidium Haitlinger, 2000, known from the southwestern Palaearctic. A comparison with related genera and species places th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Parasitengona has a distinct life cycle, including three active stages, parasitic larva and predaceous deutonymph and adult. As drastic morphological changes occur between larvae and deutonymphs, all active mite stages can be associated with each other only by rearing or DNA sequencing (Wharton & Fuller 1952; Johnston & Wacker 1967; Robaux 1974; Wohltmann 2000; Konikiewicz et al 2016; Costa et al 2019). The descriptions of most Parasitengona species are based only on either larval or post larval instars, but not both (Mąkol & Wohltmann 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Parasitengona has a distinct life cycle, including three active stages, parasitic larva and predaceous deutonymph and adult. As drastic morphological changes occur between larvae and deutonymphs, all active mite stages can be associated with each other only by rearing or DNA sequencing (Wharton & Fuller 1952; Johnston & Wacker 1967; Robaux 1974; Wohltmann 2000; Konikiewicz et al 2016; Costa et al 2019). The descriptions of most Parasitengona species are based only on either larval or post larval instars, but not both (Mąkol & Wohltmann 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Increased research on fossil arachnids in recent years (Penney 2016;Dunlop et al 2018a) has resulted in a significant increase in the number of described terrestrial Parasitengona mites (Konikiewicz & Mąkol 2014, and data summarized therein; Bartel et al 2015;Konikiewicz et al 2016aKonikiewicz et al , 2016bDunlop et al 2018b;Mąkol et al 2018). Representatives of nine out of 19 families currently assigned to terrestrial parasitengones (Mąkol & Wohltmann 2012) have been recorded from the Cretaceous, and/or Paleogene deposits.…”
Section: Introductionmentioning
confidence: 99%
“…From a total of 1828 species, it was reported that 808 are known only from larvae, 889 from active postlarval forms and 131 from both. Since 2013, 35 species have been described, of which 29 are known only from larvae, 2 from active postlarval forms and 4 from both (Sevsay & Karakurt, 2013a, b;Adil & Sevsay, 2014a, b;Mahmoudi et al, 2014;Mąkol & Sevsay, 2014;Konikiewicz & Mąkol, 2014;Kamran & Alatawi, 2014Adil et al, 2015 a, b, c, d;Karakurt & Sevsay, 2015;Karakurt et al, 2016;Mayoral & Seeman, 2015;Masoumi et al, 2016;Noei et al, 2014;Noei et al, 2015 a, b, c;Noei et al, 2017;Haitlinger & Šundić, 2015 a, b, c, d;Šundić & Haitlinger, 2015 a, b;Haitlinger et al, 2016;Konikiewicz et al, 2016;Liu & Zhang, 2016;Yazdanpanah et al, 2016;Mayoral & Barranco, 2017;Saboori et al, 2017).…”
Section: Introductionmentioning
confidence: 99%